(untitled) (Swiss Medical Weekly, 2014)
Muscular dystrophies are classically subdivided according to their clinical phenotype, and were historically defined as progressive myopathies in which muscle biopsies demonstrate muscle fibre necrosis and regeneration, as well as replacement of muscle fibres by adipose and connective tissue. In recent years, great progress has been made in identifying the genetic basis of many myopathies, thereby presenting opportunities to develop therapeutic strategies that act on specific molecular pathomechanisms. The different therapeutic strategies and their molecular targets will be reviewed.